Defining trajectories of response in patients with psoriasis treated with biologic therapies. (4th June 2021) - Geifman, N.; Azadbakht, N.; Zeng, J.; Wilkinson, T.; Dand, N.; Buchan, I.; Stocken, D.; Di Meglio, P.; Warren, R.B.; Barker, J.N.; Reynolds, N.J.; Barnes, M.R.; et al.
Summary: Background: The effectiveness and cost‐effectiveness of biologic therapies for psoriasis are significantly compromised by variable treatment responses. Thus, more precise management of psoriasis is needed. Objectives: To identify subgroups of patients with psoriasis treated with biologic therapies, based on changes in their disease activity over time, that may better inform patient management. Methods: We applied latent class mixed modelling to identify trajectory‐based patient subgroups from longitudinal, routine clinical data on disease severity, as measured by the Psoriasis Area and Severity Index (PASI), from 3546 patients in the British Association of Dermatologists Biologics and Immunomodulators Register, as well as in an independent cohort of 2889 patients pooled across four clinical trials. Results: We discovered four discrete classes of global response trajectories, each characterized in terms of time to response, size of effect and relapse. Each class was associated with differing clinical characteristics, e.g. body mass index, baseline PASI and prevalence of different manifestations. The results were verified in a second cohort of clinical trial participants, where similar trajectories following the initiation of biologic therapy were identified. Further, we found differential associations of the genetic marker HLA‐C*06:02 between our registry‐identified trajectories. Conclusions: These subgroups, defined by change in disease over time, may be indicative of distinct endotypes driven by different biological mechanisms and may help inform the management of patients with psoriasis. Future work will aim to further delineate these mechanisms by extensively characterizing the subgroups with additional molecular and pharmacological data. Abstract : What is already known about this topic? While many patients with psoriasis respond to treatment with biologics, there are those who show little or no response and those who respond initially but then either lose response or suffer from adverse effects. Better characterization of patients who will, or will not, benefit from biologic therapy will facilitate the understanding of relevant biological mechanisms and explain treatment outcome variation in patient cohorts. What does this study add? Using a data‐driven approach, we identified four subgroups of patients with psoriasis defined by global trajectories of response to biologic therapies. Our results were replicated in a second cohort obtained by pooling data from four clinical trials of biologic therapies for psoriasis. We further identified potential human leucocyte antigen biomarkers that help to distinguish between the trajectory‐based subgroups. Linked Comment: L.S. van der Schoot and J.M.P.A. van den Reek. Br J Dermatol 2021; 185 :698–699 .